USING STORYTELLING TO IMPROVE STUDENTS’ ABILITY IN SPEAKING - Utami Ratna Swari (Universitas Aki, 2022)
This research was action research. The subjects were 19 students majoring Elementary Education in B class in the academic year 2021/2022 of Panca Marga University Probolinggo. The purpose of this reseach was to find out whether or not using storytelling could improve students’ ability in speaking. This research was conducted in two (2) cycles. The procedure of each cycle consisting of:planning, acting, observing and reflecting. There were two main data gained from the research:descriptive and statistical. Descriptive data were obtained from observation, while statistical data were taken from post-test after the cycle had finished. As the criteria of success, the researcher adapted speaking scoring rubric consisting speaking aspects as follow: Comprehension, Vocabulary, Gramar, Fluency and Pronunciation. Each aspect consisted of criteria 1 until criteria 5. The result of the research was considered successful if 70 % of the students were able to reach criteria 4 in every speaking aspects. After preliminary study, cycle one was conducted. The result did not matched the criteria of success, thus cycle two was conducted. After cycle two had finished, the post-test showed major improvement, 70 % of the students reached the passing grade. It indicated that using storytelling could improve students’ ability in speaking.